2021
DOI: 10.3389/fneur.2021.744017
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Anxiety, Depression, Sleep, and Family Function in Caregivers of Children With Epilepsy

Abstract: Objective: Epilepsy is a chronic disease that places a heavy burden on caregivers. Previous studies have shown that caregivers of epilepsy patients often experience anxiety and depression; however, few comprehensive studies have assessed their sleep quality and family function. Based on the current understanding of the anxiety and depression state of caregivers in children with epilepsy, we further explored the caregivers' sleep and family function and evaluated the predictors of the depression state of caregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In the present study, the prevalence of depressive symptoms was 69.84%. A recent cross-sectional research conducted among 308 caregivers of children with epilepsy found that the proportion of depression accounts for 65.60% (18), which was consistent with our reported incidence of depression. In other studies, the prevalence of depressive symptoms ranged from 23.5 to 55% (8,9).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the prevalence of depressive symptoms was 69.84%. A recent cross-sectional research conducted among 308 caregivers of children with epilepsy found that the proportion of depression accounts for 65.60% (18), which was consistent with our reported incidence of depression. In other studies, the prevalence of depressive symptoms ranged from 23.5 to 55% (8,9).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, raising a child with severe epilepsy was highly related to caregivers' distress and depressive symptoms ( 17 ). But the latest study showed that the disease severity of CWE cannot predict parental depression in China ( 18 ). The relationship between epilepsy severity and depression is contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers' perceptions and attitudes towards epilepsy can also affect them psychologically, as caregivers often experience negative emotions (Murugupillai et al, 2016). Studies have shown that depression and anxiety are experienced by almost half of all caregivers (Zhang et al, 2021). Carers may experience anxiety over various aspects of the condition, including physical, behavioural and cognitive function, psychological and social function, educational performance, and the future with regard to epilepsy and its management (Murugupillai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An increased level of self-stigmatization is associated with low socioeconomic status [7], difficulties with employment, low level of medical literacy, failure to follow the prescribed treatment, concealment of the diagnosis, number of seizures [8]. The existence of intrapersonal conflicts, aggression, dysphoric disorder, depressive disorder in patients with epilepsy [9,10,11], causes the occurrence of frequent and regular conflict situations in the family and in the professional sphere of these patients, which naturally worsens their social adaptation in modern society, and requires professional intervention in the form of rehabilitation and psychocorrectional measures [12,13,14].…”
Section: Introductionmentioning
confidence: 99%